2005
DOI: 10.1167/iovs.05-0343
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of p63 Combined with a Large N/C Ratio Defines a Subset of Human Limbal Epithelial Cells: Implications on Epithelial Stem Cells

Abstract: These results suggest that this distinct group of small cells in the limbal epithelium with greater N/C ratio, expressing high levels of nuclear protein p63, probably represent corneal epithelial stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 28 publications
(41 reference statements)
8
83
1
1
Order By: Relevance
“…Fresh enucleated cadaver globes of donors below 75 years of age, without any evidence of trauma or surgery were procured within six hours of death from the Rotary Aravind International Eye Bank at Aravind Eye Hospital, Madurai. 13 Histology and immunostaining-Tangential sections of paraffin embedded corneolimbal tissues from three different donors were stained with haematoxylin-eosin following standard methods. For immunostaining, serial 5 μm cryosections of corneo-limbal tissues were processed as described earlier.…”
Section: Confocal Microscopic Analysis Of Immunostained Cadaver Cornementioning
confidence: 99%
See 1 more Smart Citation
“…Fresh enucleated cadaver globes of donors below 75 years of age, without any evidence of trauma or surgery were procured within six hours of death from the Rotary Aravind International Eye Bank at Aravind Eye Hospital, Madurai. 13 Histology and immunostaining-Tangential sections of paraffin embedded corneolimbal tissues from three different donors were stained with haematoxylin-eosin following standard methods. For immunostaining, serial 5 μm cryosections of corneo-limbal tissues were processed as described earlier.…”
Section: Confocal Microscopic Analysis Of Immunostained Cadaver Cornementioning
confidence: 99%
“…For immunostaining, serial 5 μm cryosections of corneo-limbal tissues were processed as described earlier. 13 The primary antibodies used were Thy 1 mouse monoclonal IgG 1 (CD 90) or endoglin mouse monoclonal IgG 1 (CD 105).…”
Section: Confocal Microscopic Analysis Of Immunostained Cadaver Cornementioning
confidence: 99%
“…It has been shown that a significantly higher level of p63 found in limbal stem cells is important in the maintenance of pluripotency of these cells and that it plays an important role in the development of corneal epithelia (33,34). In the study, human and mouse limbal stem/progenitor cells were carefully monitored by detection of p63 expression levels and compared with center corneal epithelial cells.…”
Section: Mef Cells Obtained From Plk3mentioning
confidence: 99%
“…Such immunologically based cell-enrichment techniques, while useful, are limited by the need for appropriate cell-type-specific antibodies. Antibodies against the ATPbinding cassettes subfamily G member 2 (ABCG2) and subfamily B member 5 (ABCB5) have been successfully used to enrich the LSC population, but they also enrich for other ABCG2-or ABCB5-expressing cells present in the limbus and cornea (11,(14)(15)(16). The use of antibodies to identify LSCs in the clinic is cumbersome, requiring~15 h of laborious cell processing, and can subsequently affect cellular physiology if the epitope is associated with a functionally important protein domain (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in biomechanical properties during stem cell differentiation could enable microfluidic approaches for on-the-fly analysis and sorting of stem cells from differentiated cells. Although LSCs have been characterized by a small diameter and high nucleus/cytoplasm ratio in comparison with other cells from the limbal region (14,21,25), a complete biophysical characterization of LSCs in relation to the surrounding corneal cells has not yet been achieved.…”
Section: Introductionmentioning
confidence: 99%